ONOMASTICS STUDY FOR CATS GIVEN NAMES IN JORDAN - JABER, MAISA S (International Journal of Psychosocial Rehabilitation, 2020)
The study reported here is within the field of Onomastics that explores pet cat given names in one Arabic speaking community. To achieve the goal of the study, 153 pet cat names were collected through the means of a questionnaire distributed on the Facebook page Ask Jordan. The study shows that the names of cats in Jordan can be classified into different categories: the cat’s appearance, cartoon or movie character references, the cat’s gender, classic names, new names and finally, circumstantial names. Moreover, the study reveals that stray cats can have different names from purebred house cats. Finally, the study suggests that future research should examine pet cat names in other countries.